Titin-Actin Interaction: PEVK-Actin-Based Viscosity in a Large Animal. (13th September 2011) - Chung, Charles S.; Bogomolovas, Julius; Gasch, Alexander; Hidalgo, Carlos G.; Labeit, Siegfried; Granzier, Henk L.
Abstract : Titin exhibits an interaction between its PEVK segment and the actin filament resulting in viscosity, a speed dependent resistive force, which significantly influences diastolic filling in mice. While diastolic disease is clinically pervasive, humans express a more compliant titin (N2BA:N2B ratio ~0.5–1.0) than mice (N2BA:N2B ratio ~0.2). To examine PEVK-actin based viscosity in compliant titin-tissues, we used pig cardiac tissue that expresses titin isoforms similar to that in humans. Stretch-hold experiments were performed at speeds from 0.1 to 10 lengths/s from slack sarcomere lengths (SL) to SL of 2.15  μ m. Viscosity was calculated from the slope of stress-relaxation vs stretch speed. Recombinant PEVK was added to compete off native interactions and this found to reduce the slope by 35%, suggesting that PEVK-actin interactions are a strong contributor of viscosity. Frequency sweeps were performed at frequencies of 0.1–400 Hz and recombinant protein reduced viscous moduli by 40% at 2.15 μ m and by 50% at 2.25 μ m, suggesting a SL-dependent nature of viscosity that might prevent SL "overshoot'' at long diastolic SLs. This study is the first to show that viscosity is present at physiologic speeds in the pig and supports the physiologic relevance of PEVK-actin interactions in humans in both health and disease.